Factors associated with cancer-related fatigue in breast cancer patients undergoing endocrine therapy in an urban setting: a cross-sectional study - Huang, Xu (BioMed Central, 2010)
BACKGROUND: Fatigue is prevalent in breast cancer survivors and has profound effects on daily life. The interference of fatigue with endocrine therapy may be difficult to separate. This study investigates the prevalence and severity of fatigue and identifies the demographic, clinical, and lifestyle factors associated with cancer-related fatigue (CRF) in breast cancer patients undergoing endocrine therapy in an urban area. METHODS: Women with stage I-IIIA breast cancer were recruited and asked to participate (n = 371) in the study. The 315 women who responded to the questionnaire (84.9%), 54 (17.1%) had completed endocrine therapy and 261 (82.9%) were still undergoing endocrine therapy. The patients had been diagnosed at an average of 31 months prior to recruitment (range, 7 to 60 months); the average age was 48 (range, 33 to 72) years. The 11-point scale and Visual Analog Scale (VAS) were employed to quantify the level of fatigue experienced by the patients. Logistic regression analyses and a trend test method were performed to evaluate factors associated with CRF. RESULTS: Among the 315 patients, 189 (60%) had experienced or were experiencing CRF during endocrine therapy. Logistic regression analysis was performed to identify factors associated with CRF, including BMI (body mass index), clinical stage, menopausal status, duration of endocrine therapy, physical activity, and diet. Factors unrelated to CRF were age, marital status, treatment, endocrine therapy drugs, alcohol intake, and smoking. The trend test method revealed an association between physical activity and dietary level and the intensity of CRF. CONCLUSIONS: The present findings suggest that fatigue is an important problem in the majority of breast cancer patients during endocrine therapy. We found that BMI, clinical stage, menopausal status, duration of endocrine therapy, physical activity, and diet are associated with fatigue. Future research should focus on the impact factors of CRF and lifestyle in the management of breast cancer patients.